Antioxidant Enzymes Haplotypes and Polymorphisms Associated with Obesity in Mexican Children - Paula Costa-Urrutia; Aline Mariana Flores-Buendía; Iván Ascencio-Montiel; Jacqueline Solares-Tlapechco; Omar Noel Medina-Campos; José Pedraza-Chaverri; Julio Granados; Angélica Saraí Jiménez-Osorio; Martha Eunice Rodríguez-Arellano (Antioxidants, 2020)
Obesity is a major health problem worldwide and constitutes a sanitary emergency in Mexico, especially childhood obesity. Several studies have proved the relationship between obesity and oxidative stress and the influence of genetic predisposition. This work was aimed to analyze the association of antioxidant enzyme polymorphisms with overweight and obesity in Mexican children and adolescents. A case-control study was performed in 585 children and adolescents aged 3 to 17 years, using two criteria to classify obesity: body mass index (BMI) and body fat percentage (BFP). Anthropometric and biochemical measurements were carried out, and malondialdehyde serum levels were determined. Genotyping was done with the Axiom Genome-Wide LAT microarray, including 68 single nucleotide polymorphisms (SNPs) of the glutathione peroxidase (GPX) and paraoxonase (PON) families. We found six haplotypes associated with obesity—two of them (one in GPX3 and the other in GPX5 and GPX6) in a protective direction when obesity was classified by BMI. The other four haplotypes were associated with obesity when classification was based on BFP—one of them in GPX3 in a protective direction and the others in PON genes conferring obesity risk. In addition, two SNPs, GPX3 rs922429 and GPX4 rs2074451 showed protection against obesity classified by BFP. This study showed genetic susceptibility to oxidative stress in relation to obesity in Mexican children and opens up the possibility that some genetic loci related to obesity are not identified when weight classification is based on BMI.